1990
DOI: 10.1097/00004032-199011000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Meteorological Modeling of Arrival and Deposition of Fallout at Intermediate Distances Downwind of the Nevada Test Site

Abstract: A three-dimensional atmospheric transport and diffusion model is used to calculate the arrival and deposition of fallout from 13 selected nuclear tests at the Nevada Test Site (NTS) in the 1950s. Results are used to extend NTS fallout patterns to intermediate downwind distances (300 to 1200 km). The radioactive cloud is represented in the model by a population of Lagrangian marker particles, with concentrations calculated on an Eulerian grid. Use of marker particles, with fall velocities dependent on particle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 0 publications
3
23
0
Order By: Relevance
“…Particle sizes and release heights for the Harry simulation closely followed those selected by Cederwall and Peterson (1990). Trajectory endpoint calculations and fallout pattern plots produced by Cederwall and Peterson (1990) indicated two diverging air masses at approximately H+10 hours downwind.…”
Section: Nuclear Test Simulations and Model Evaluationsmentioning
confidence: 64%
See 3 more Smart Citations
“…Particle sizes and release heights for the Harry simulation closely followed those selected by Cederwall and Peterson (1990). Trajectory endpoint calculations and fallout pattern plots produced by Cederwall and Peterson (1990) indicated two diverging air masses at approximately H+10 hours downwind.…”
Section: Nuclear Test Simulations and Model Evaluationsmentioning
confidence: 64%
“…More sophisticated simulations of the distribution of activity in the cloud and on various size particles have been done in other studies (see for example, Cederwall and Peterson 1990). However, since the particle-size and activity distributions can vary significantly with the particular conditions of a test such as height of burst, type of soil, and yield (see companion paper by Ibrahim et al 2010), even simulations using more elaborate models (see for example, Cederwall and Peterson 1990), were forced to adjust the activity, altitude, and particle size parameter estimates for each test to achieve even marginal agreement with actual measurements.…”
Section: Nuclear Test Simulations and Model Evaluationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies performed as part of the ORERP found that it was not possible to reproduce fallout patterns with primary input data. However, it was found that meteorological models were useful tools in extending known patterns downwind (Cederwall and Peterson 1990). One reason 1 for the failure of models of atmospheric transport in this case was the episodic and short-term nature of the releases.…”
Section: Methods Of Dose Reconstructionmentioning
confidence: 99%